Perancangan Wayfinding Kebun Raya Indrokilo Boyolali - Shalahuddin, Sayyid Mahdi; Lukitasari, Evelyne Henny; Wibowo, Yudi (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2024)
Abstract The arrangement of public space needs a modern way, such as wayfinding media. It is because people's lifestyles are becoming more practical, effective and efficient. The Indrokilo Boyolali Botanical Garden is one of the tourist attractions in Boyolali that requires wayfinding of the Indrokilo Boyolali Botanical Garden. It is due to there is no clear and communicative information system. Therefore, it is difficult for tourists to know and recognize the destination of a place or a road. The application of a wayfinding system, information design, and exhibition design is in accordance with the needs of the Indrokilo Boyolali Botanical Garden. The Wayfinding design used the Icon Pictogram technique for all visual elements to have uniformity in shape and colour elements for easy recognition. In addition, it is also in accordance with geographical conditions in tourist areas that attract tourists to visit. Keywords: Wayfinding, Information System, Tourism, Indrokilo Boyolali Botanical Garden, Icon Pictogram